Simulation of Smart Speed Variation in Electric Vehicles Using Fuzzy Logic Controller - Imo, Felix Udobi; Aluhumile, Erukpe P.; A., Nwabueze C. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Roads today are often equipped with speed breakers, which, although intended to control vehicle speed and reduce accidents, frequently cause inconvenience and potential hazards, especially when drivers encounter them unexpectedly. Speed breakers were introduced to curb the risks of collisions due to overspeeding; however, their physical implementation can disrupt vehicle movement and comfort. This study proposes a smart speed variation system for electric vehicles using a Fuzzy Logic Controller, aimed at eliminating the need for physical speed bumps while ensuring road safety. In the proposed system, a transmitter is placed at the entry point of a road segment with a designated speed limit. This transmitter sends a specific frequency corresponding to the speed limit, which is received by oncoming vehicles equipped with a compatible receiver. Upon receiving the signal, the vehicle automatically adjusts its speed to comply with the set limit. When the vehicle exits the restricted zone, it receives another signal permitting it to resume normal speed. This intelligent speed control system enhances driving comfort, ensures safety by maintaining regulated speeds, and contributes to energy efficiency in electric vehicles. The system was developed and simulated using MATLAB/Simulink with fuzzy logic to handle the dynamic control of vehicle speed based on environmental inputs. The simulation results confirm that speed variation can be effectively achieved through vehicle-to-infrastructure communication, demonstrating a viable alternative to traditional speed control mechanisms.